Precetion of Stress and Satisfaction among Student Traditionl to Online Classroom - Mariya Tariq, Misbah Waris, Mehreen Mazhar, Rida Mubashir, Sumbal Mushtaq, Sadaf Waris, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Online education is a newer strategy of imparting knowledge .it is two_ way and involves both teachers and students in a virtual environment. Recently, there has been a booming escalation in efforts to shift traditional classrooms into virtual ones. But this has not come without challenges to both teachers and students. Objective: The purpose of current research is determining the level of satisfaction a stress in the students due to the shift from traditional to online classroom. Methodology: This Research reports research from students from medical colleges and universities in an attempt to determine satisfaction and stress due to online in higher education. The sample size was calculated to be N=206.As per inclusion criteria, members of STUDENTS from Lahore, who had previous experience in traditional classes for at least 3 months, Students who had traditional experience of less than 3 months were excluded. Frequencies were calculated to find out prevalence of stress and satisfaction among students after transition of traditional to online classrooms. Results: More than half of the students were satisfied with the online learning and the students have a moderate level of stress during E Learning . Approximately 75% of students agreed that at times it was stressful. One line learning is enhances their self studying habit’(88.1%).Most of the students were pleased with the response of the departments concerned to any problems in the online tests ,classes, and course material. Conclusion: Although recently adopted, the satisfaction of the students towards online classes appears good and prioritizing the identified predictors and working on the weal; inks could assist in enhancing student’s satisfaction an better outcomes.